Opioid Overdose Crisis Prevention in Riley County - Blattner, Brittany (My University, 2020)
According to the Centers for Disease Control and Prevention (CDC), since 1999 drug overdose deaths involving opioids have increased nearly six times. In 2018, opioids were involved in almost 47,000 overdose deaths in the United States. Over the past two decades the U.S. has experienced a crisis of opioid addiction and overdose that has escalated at an alarming rate. In recent years the CDC has responded through the implementation of both public awareness and health professional education campaigns. In 2018, the CDC promoted prevention on a local level by awarding grant funds to county health departments under the Opioid Overdose Crisis Response Cooperative Agreement. Riley County was one of the recipients of this grant, and over a nine-month period, myself and my colleagues worked under this agreement to improve opioid addiction awareness and prevent overdose in the community. Our work included the completion of a community needs assessment, regular contact and collaboration with first responders, law enforcement, and healthcare providers, the implementation and assessment of a public awareness ad campaign, promotion of referral to treatment and prescription drug monitoring programs among local healthcare providers, promotion of services for at-risk community members, and providing relevant training sessions to healthcare providers, first responders, and community members. We found that our efforts served as a timely resource for professionals serving citizens in crisis and engaged the community in conversation and awareness of this epidemic.
Keywords: Opioid; health department; addiction; overdose; Riley County Kansas; Ad campaign